PENERAPAN APLIKASI MOODLE SEBAGAI SALAH SATU MODEL PEMBELAJARAN JARAK JAUH DI MASA PANDEMI - Widiatmoko Herbimo (Ideguru: Jurnal Karya Ilmiah Guru, 2020)
Education is a factor that determines human welfare so that it can be used as an indicator of the progress of a nation and state. The higher the quality of education of a nation and country, it is certain that the more developed and prosperous the nation and country will be. Educators are expected to be able to change the old paradigm in teaching, namely to convey as many lessons as possible with a new paradigm that emphasizes efforts to help students to be better able to understand, comprehend, or master concepts to solve a problem. The model uses a moodle application that offers a pleasant learning atmosphere, so students are invited to practice growing curiosity, responsibility, honesty and activeness of students. Moodle is a software package produced for internet-based learning activities and websites that use social constructionist pedagogy principles. Moodle is one of the applications of the concepts and mechanisms of teaching and learning that utilize information technology, which is known as the concept of electronic learning or e-learning. Moodle application is very good and interactive in online learning, thus making students not bored in distance learning during the pandemic.